Pemulihan Elia sebagai Model Teologis-Psikologis bagi Intervensi Depresi Pada Remaja - Yustinus, Yustinus (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2025)
Depression was a form of mental health disorder that was widely experienced by adolescents in Indonesia, influenced by biological, psychological, social, and spiritual factors. Treatment that focused on clinical and psychological aspects was indeed beneficial, yet it often did not address the spiritual dimension that could support holistic recovery. This study aimed to develop a theologically and psychologically informed intervention model based on the narrative of Elijah’s restoration in 1 Kings 19 to support adolescents experiencing depression holistically. The research employed a qualitative approach with library research, integrating biblical exegesis, pastoral theology literature, and adolescent psychospiritual theories. The findings indicated that integrated physical, emotional, and spiritual recovery enhanced adolescents’ psychological resilience, reduced depressive symptoms, and fostered meaning and hope. This model held practical implications for counselors, pastors, and Christian educational institutions in designing contextual and holistic interventions for adolescent depression. Thus, the study affirmed that Elijah’s restoration narrative could serve as an applicable theological-psychological framework for adolescent depression interventions.AbstrakDepresi sebagai bentuk gangguan kesehatan mental yang banyak dialami oleh remaja di Indonesia, dipengaruhi oleh faktor biologis, psikologis, sosial, dan spiritual. Penanganan yang berfokus pada aspek klinis dan psikologis memang bermanfaat, namun kerap belum menyentuh dimensi spiritual yang dapat mendukung pemulihan secara holistik. Penelitian ini bertujuan mengembangkan model intervensi teologis-psikologis berbasis narasi pemulihan Elia dalam 1 Raja-Raja 19 untuk mendampingi remaja yang mengalami depresi secara holistik. Penelitian menggunakan pendekatan kualitatif dengan studi pustaka, mengintegrasikan eksposisi Biblika. Hasil penelitian menunjukkan bahwa pemulihan fisik, emosional, dan spiritual yang terintegrasi mampu meningkatkan ketahanan psikologis remaja, menurunkan gejala depresi, dan membangun makna serta harapan. Model ini memiliki implikasi praktis bagi konselor, pendeta, dan lembaga pendidikan Kristen dalam merancang intervensi depresi remaja yang kontekstual dan holistik.Dengan demikian, penelitian ini menegaskan bahwa narasi pemulihan Elia dapat menjadi kerangka konseptual teologis-psikologis yang aplikatif bagi intervensi depresi remaja.